The birth of Dionysus in Euripides’ "Bacchae": Cadmo’s and Tiresias’ opinions - Macías Otero, Sara (’Ilu. Revista de Ciencias de las Religiones, 2019)
The main theme of Euripides’ Bacchae is Dionysus’ divinity and its recognition by the Thebans. The birth of Dionysus is a key point in the myth to determine that he is a god, consequently the playwright makes several of his characters mention it from different points of view. There are two versions clearly in conflict: on the one hand, Dionysus and his worshippers defend that he is a son of Zeus and, therefore, a god who must be venerated. On the other hand, Pentheus, assuming his aunts’ view, thinks that his aunt Semele, who is Dionysus’ mother, lied when she stated that she had conceived a son of Zeus, in order to conceal a love affair with a mere mortal. Therefore, in the king’s opinion Dionysus is not a god but a mere human being. In addition, there are two characters, Cadmus and Tiresias, whose attitudes with regard to this matter are not so clear and have led scholars to interpret them in opposite ways. In this paper I am analyzing the passages of Bacchae on Dionysus’ birth, with special emphasis on those where Euripides shows or refers to Cadmus’ and Tiresias’ opinions, since my aim is to try to clarify, as far as possible, which stand the playwright made those two characters adopt regarding to Dionysus’ divinity.